Barbell hip thrust, muscular activation and performance: A systematic review - Krause Neto, W.; Lima Vieira, T.; Gama, F. (Journal of Sports Science & Medicine, 2019)
The present systematic review aimed to analyze the activation of the muscles involved in the barbell hip thrust (BHT) and its transfer to sports activities that include horizontal displacement. A search of the current literature was performed using the PubMed, SPORTDiscuss, Scopus and Google Scholar databases. The inclusion criteria were: (a) descriptive studies, (b) physically trained participants, (c) analyzed muscle activation using normalized EMG signals or as a percentage of maximal voluntary isometric contraction (MVIC) and (d) acute or chronic transfer of the BHT to horizontal displacement activity. Twelve articles met the inclusion criteria and the following results were found: 1) neuromuscular activation: hip extensor muscles (gluteus maximus and biceps femoris) demonstrated greater activation in the BHT compared to the squat. The straight bar deadlift exercise demonstrated greater biceps femoris activation than BHT; 2) Regardless of the BHT variation and intensity used, the muscle excitation sequence is gluteus maximus, erector spinae, biceps femoris, semitendinosus, vastus lateralis, gluteus medius, vastus medialis and rectus femoris; 3) acute transfer: four studies demonstrated a significant improvement in sprinting activities after BHT exercise; 4) as for the chronic transfer: two studies demonstrated improvement of the sprint time, while other two studies failed to present such effect. We concluded that: a) the mechanics of BHT favors greater activation of the hip extensor muscles compared to more conventional exercises; b) regardless of the variation of BHT used, the muscle excitation sequence is gluteus maximus, erector spinae, hamstrings, and quadriceps femoris; c) the acute transfer of the post-activation potentiation of the BHT is significant, improving the sprinting time; and d) despite training with BHT submaximal loads can improve sprint times, further investigations are needed.